2018
DOI: 10.1128/aac.00725-18
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Phenotypic High-Content Imaging Assay for Assessing the Antiviral Activity of Small-Molecule Inhibitors Targeting Zika Virus

Abstract: Zika virus (ZIKV) has been linked to the development of microcephaly in newborns, as well as Guillain-Barré syndrome. There are currently no drugs available to treat ZIKV infection, and accordingly, there is an unmet medical need for the discovery of new therapies. High-throughput drug screening efforts focusing on indirect readouts of cell viability are prone to a higher frequency of false positives in cases where the virus is viable in the cell but the cytopathic effect (CPE) is reduced or delayed. Here, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Ribavirin is a well-known nucleotide analog and its anti-flavivirus activity has previously been reported [20,35]. Ribavirin showed moderate anti-ZIKV activity in our assay (EC 50 value of 45.5 ± 13.5 µM and EC 90 value of 114.5 ± 18.0 µM), consistent with previous reports displaying a variable efficacy range of ribavirin against ZIKV (EC 50 between 20 and 48 µM) [37][38][39]. Favipiravir failed to display anti-ZIKV activity in our assay.…”
Section: Discussionsupporting
confidence: 91%
“…Ribavirin is a well-known nucleotide analog and its anti-flavivirus activity has previously been reported [20,35]. Ribavirin showed moderate anti-ZIKV activity in our assay (EC 50 value of 45.5 ± 13.5 µM and EC 90 value of 114.5 ± 18.0 µM), consistent with previous reports displaying a variable efficacy range of ribavirin against ZIKV (EC 50 between 20 and 48 µM) [37][38][39]. Favipiravir failed to display anti-ZIKV activity in our assay.…”
Section: Discussionsupporting
confidence: 91%
“…The (3R,4R,5R)-5-(benzoyloxy)methyl)-3-ethynyltetrahydrofuran-2,3,4-triyl tribenzoate 1 was synthesized by following a previously reported procedure [27]. Synthetic details for aryloxy phosphoramidate ProTides other than for 2′- C -ethynyluridine and 2′- C -ethenyluridine were published previously by our group [24]. All reactions were carried out in either an oven-dried round bottom flask or a Schlenk tube under a nitrogen atmosphere using commercially available anhydrous solvents and monitored by thin-layer chromatography with detection by UV light.…”
Section: Methodsmentioning
confidence: 99%
“…Further, sofosbuvir is the only FDA approved inhibitor tested against ZIKV thus far in ProTide form. In addition, recent work by our group and others has suggested that sofosbuvir and ProTides in general have differential activity depending on the cell line used, which may be linked to the cell-specific metabolism of ProTides [17,24]. In this work, we chemically synthesized a library of 13 ProTides and tested them for activity against ZIKV in human neural stem cells, a disease-specific cell model of infection.…”
Section: Introductionmentioning
confidence: 99%
“…HCI was developed with the contribution of major advances in robotics, imaging and automated image processing (Moffat et al, 2017). HCI is already a fundamental technology for antiviral screening and validation (Bernatchez et al, 2018;Hoenen, 2017;Lowen et al, 2018;Mudhasani et al, 2014;Panchal et al, 2010;Tan et al, 2014).…”
Section: Imaging For Studying Antiviralsmentioning
confidence: 99%